2007
DOI: 10.1080/15569520701212399
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous and Ocular Late Complications of Sulfur Mustard in Iranian Veterans

Abstract: Although sulfur mustard (SM) has been used as a chemical warfare agent since the early twentieth century, it has reemerged in the past decade as a major threat around the world. This agent injured over 100,000 Iranians and one-third is suffering from late effects until today. Mustard affects many organs such as the skin, eyes, and lungs, as well as the gastrointestinal, endocrine, and hematopoietic system. In this study we focused on review of the late Cutaneous and ocular complications caused by exposure to S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
68
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 26 publications
2
68
0
Order By: Relevance
“…The most common skin complaints among patients were itching followed by burning sensation and desquamation. These symptoms are due to dryness of the skin, thus become worse in dry weather and after physical activity [8,12]. Comparison with other studies showed an increase in the frequency of itching and dry skin.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…The most common skin complaints among patients were itching followed by burning sensation and desquamation. These symptoms are due to dryness of the skin, thus become worse in dry weather and after physical activity [8,12]. Comparison with other studies showed an increase in the frequency of itching and dry skin.…”
Section: Discussionmentioning
confidence: 86%
“…This may be due to the warm and dry climate of Shiraz. Pruritus is the most common complication reported in most studies [3,4,12]. Panahi et al reported that 53% of SM-intoxicated patients had severe pruritus, resulting in a significant negative impact on quality of life [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the Iraqi use of SM in the 1985-1988 Iran-Iraq war prompted Iranian ophthalmologists to record the range of ocular injuries incurred by their exposed troops. [4][5][6][7][8][9][10][11][12] This has highlighted the global need for ocular therapies against SM exposure. Even after 100 years of study, there are still no U.S. Food and Drug Administration (FDA)-approved countermeasures against vesicant exposures, whether to the eye, skin, or lung.…”
mentioning
confidence: 99%
“…37,41,42 the development of delayed lSCD following Sm was described in details in the literature in experimental models 43,44 and in human victims. [45][46][47][48] although the mechanism of the delayed-onset lSCD is still not entirely clear, recent studies on the pathogenesis of Sm-induced ocular lesions increase our knowledge on the pathogenesis of this unique type of lSCD and may be helpful in understanding the mechanism underlying the injuries of other chemicals belonging to this category.…”
Section: Delayed-onset Lscd Following Chemical Injurymentioning
confidence: 99%